2019
DOI: 10.1111/mmi.14238
|View full text |Cite
|
Sign up to set email alerts
|

A non‐coding RNA from the intercellular adhesion (ica) locus of Staphylococcus epidermidis controls polysaccharide intercellular adhesion (PIA)‐mediated biofilm formation

Abstract: Polysaccharideintercellular adhesin (PIA)associated biofilm formation is mediated by the intercellular adhesin (ica) locus and represents a major pathomechanism of Staphylococcus epidermidis. Here, we report on a novel long non-coding (nc)RNA, named IcaZ, which is approximately 400 nucleotides in size. icaZ is located downstream of the ica repressor gene icaR and partially overlaps with the icaR 3ʹ UTR. icaZ exclusively exists in icapositive S. epidermidis, but not in S. aureus or other staphylococci. Inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Moreover, recent findings also add non-protein factors to the list of PIA regulators. IcaZ, a non-coding 400-nucleotide RNA, which is encoded downstream of icaR , was found to inhibit icaR mRNA translation, leading to increased PIA production [95] . IcaZ is found inclusively in ica -positive S. epidermidis but no other staphylococcal species [95] .…”
Section: Regulation Of Pia Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, recent findings also add non-protein factors to the list of PIA regulators. IcaZ, a non-coding 400-nucleotide RNA, which is encoded downstream of icaR , was found to inhibit icaR mRNA translation, leading to increased PIA production [95] . IcaZ is found inclusively in ica -positive S. epidermidis but no other staphylococcal species [95] .…”
Section: Regulation Of Pia Biosynthesismentioning
confidence: 99%
“…IcaZ, a non-coding 400-nucleotide RNA, which is encoded downstream of icaR , was found to inhibit icaR mRNA translation, leading to increased PIA production [95] . IcaZ is found inclusively in ica -positive S. epidermidis but no other staphylococcal species [95] . Additionally, a regulatory RNA named RsaE binds in its processed form to the 5′UTR of the icaR mRNA, also increasing PIA production [96] .…”
Section: Regulation Of Pia Biosynthesismentioning
confidence: 99%
“…The results obtained herein demonstrated that a fed-batch system is only reliable in obtaining Brc from S. epidermidis biofilms for some isolates, especially from those who can form thick and strong biofilms. While all ica + isolates used herein were found to be high biofilm producing strains, it should be noted that some ica + isolates lack a functional intact operon (Cafiso et al, 2004;Cue, Lei & Lee, 2012), and the mere presence of the gene might not be related to its expression (Freitas et al, 2017;Lerch et al, 2019). As such, to assess the feasibility of this method in more strains, it is important not only to determine the presence of ica but to assess if the operon is functional, as mutations in major biofilm regulators may influence the dynamics of Brc production (Cue, Lei & Lee, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Importantly, this bacterium, which was previously seen as a commensal microorganism due to its benign relationship with the host (Cogen, Nizet & Gallo, 2008;Gardiner et al, 2017), is nowadays accepted as an important opportunistic pathogen, of particular concern in ill and immunocompromised patients (Otto, 2009). S. epidermidis infections are more likely to happen upon invasive procedures involving indwelling medical devices, in which the physiological barriers are compromised, since this bacterium is a ubiquitous inhabitant of the skin and mucosae in humans (Ziebuhr et al, 2006) and has a strong ability to form biofilms on the surface of medical devices (Cerca et al, 2005c;Laverty, Gorman & Gilmore, 2013). Bacteria within biofilms are undoubtedly more resistant to antibiotics (Albano et al, 2019;Cerca et al, 2005a;Dias et al, 2018) and to the host immune defense (Cerca et al, 2006;Gray et al, 1984;Yao, Sturdevant & Otto, 2005), contributing to the persistence and recurrence of infections (Mah, 2012;Schommer et al, 2011;Singh & Ray, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained herein demonstrated that a fed-batch system is only reliable in obtaining Brc from S. epidermidis biofilms for some isolates, especially from those who can form thick and strong biofilms. While all ica + isolates used herein were found to be high biofilm producing strains, it should be noted that some ica + isolates lack a functional intact operon (Cafiso et al, 2004;Cue et al, 2012), and the mere presence of the gene might not be related to its expression (Freitas et al, 2017;Lerch et al, 2019). As such, to assess the feasibility of this method in more strains, it is important not only to determine the presence of ica but to assess if the operon is functional, as mutations in major biofilm regulators may influence the dynamics of Brc production (Cue et al, 2012).…”
Section: Discussionmentioning
confidence: 90%